Tacky the penguin - Lester, Helen; Munsinger, Lynn (Boston : Houghton Mifflin Co., 1988)
Tacky the penguin does not fit in with his sleek and graceful companions, but his odd behavior comes in handy when hunters come with maps and traps.
Book Links (A.L.A.)
Booklist
Bulletin (Center for Childrens's books)
2.0
K-3
Keywords: Penguins -- Fiction; Behavior -- Fiction; Individuality -- Fiction; Penguins -- Fiction; Individuality -- Fiction